Biochemical and biophysical properties of interactions between subunits of the peripheral stalk region of human V-ATPase. - Suhaila Rahman; Ichiro Yamato; Shinya Saijo; Kenji Mizutani; Yoshiko Ishizuka-Katsura; Noboru Ohsawa; Takaho Terada; Mikako Shirouzu; Shigeyuki Yokoyama; So Iwata; Takeshi Murata (PLoS ONE)
Peripheral stalk subunits of eukaryotic or mammalian vacuolar ATPases (V-ATPases) play key roles in regulating its assembly and disassembly. In a previous study, we purified several subunits and their isoforms of the peripheral stalk region of Homo sapiens (human) V-ATPase; such as C1, E1G1, H, and the N-terminal cytoplasmic region of V(o), a1. Here, we investigated the in vitro binding interactions of the subunits at the stalk region and measured their specific affinities. Surface plasmon resonance experiments revealed that the subunit C1 binds the E1G1 heterodimer with both high and low affinities (2.8 nM and 1.9 µM, respectively). In addition, an E1G1-H complex can be formed with high affinity (48 nM), whereas affinities of other subunit pairs appeared to be low (∼0.21-3.0 µM). The putative ternary complex of C1-H-E1G1 was not much strong on co-incubation of these subunits, indicating that the two strong complexes of C1-E1G1 and H-E1G1 in cooperation with many other weak interactions may be sufficiently strong enough to withstand the torque of rotation during catalysis. We observed a partially stable quaternary complex (consisting of E1G1, C1, a1(NT), and H subunits) resulting from discrete peripheral subunit interactions stabilizing the complex through their intrinsic affinities. No binding was observed in the absence of E1G1 (using only H, C1, and a1(NT)); therefore, it is likely that, in vivo, the E1G1 heterodimer has a significant role in the initiation of subunit assembly. Multiple interactions of variable affinity in the stalk region may be important to the mechanism of reversible dissociation of the intact V-ATPase.